Correlates of Canadian mothers' anger during the postpartum period: a cross-sectional survey - Christine HK Ou; Wendy A. Hall; Paddy Rodney; Robyn Stremler (BMC, 2022)
Abstract Background Although some women experience anger as a mood problem after childbirth, postpartum anger has been neglected by researchers. Mothers' and infants' poor sleep quality during the postpartum period has been associated with mothers' depressive symptoms; however, links between mothers' sleep quality and postpartum anger are unclear. This study aimed to determine proportions of women with intense anger, depressive symptoms, and comorbid intense anger and depressive symptoms, and to examine mothers' and infants' sleep quality as correlates of postpartum anger. Methods This cross-sectional survey study was advertised as an examination of mothers' and babies' sleep. Women, with healthy infants between 6 and 12 months of age, were recruited using community venues. The survey contained validated measures of sleep quality for mothers and infants, and fatigue, social support, anger, depressive symptoms, and cognitions about infant sleep. Results 278 women participated in the study. Thirty-one percent of women (n = 85) reported intense anger (≥ 90th percentile on State Anger Scale) while 26% (n = 73) of mothers indicated probable depression (>12 on Edinburgh Postnatal Depression Scale). Over half of the participants rated their sleep as poor (n = 144, 51.8%). Using robust regression analysis, income (β = -0.11, p < 0.05), parity (β = 0.2, p < 0.01), depressive symptoms (β = 0.22, p < 0.01), and mothers' sleep quality (β = 0.10, p < 0.05), and anger about infant sleep (β = 0.25, p < 0.01) were significant predictors of mothers' anger. Conclusions Mothers' sleep quality and anger about infant sleep are associated with their state anger. Clinicians can educate families about sleep pattern changes during the perinatal time frame and assess women's mood and perceptions of their and their infants' sleep quality in the first postpartum year. They can also offer evidence-based strategies for improving parent-infant sleep. Such health promotion initiatives could reduce mothers' anger and support healthy sleep.